2019
DOI: 10.1371/journal.pntd.0007708
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis and tumor necrosis factor alpha antagonists in the Mediterranean basin. A switch in clinical expression

Abstract: BackgroundTumor necrosis factor alpha (TNF-α) blockers are recognized as a risk factor for reactivation of granulomatous infections. Leishmaniasis has been associated with the use of these drugs, although few cases have been reported.MethodologyWe performed a retrospective observational study including patients with confirmed leishmaniasis acquired in the Mediterranean basin that were under TNF-α blockers therapy at the moment of the diagnosis. Patients diagnosed in our hospital from 2008 to 2018 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 66 publications
1
27
0
8
Order By: Relevance
“…Several common themes appear to have emerged, including an association with all forms of leishmaniasis, a generally typical disease presentation, a prolonged interval period between TNF-α inhibitor initiation and symptomatic disease onset (median of 18 months in one series), and a relatively greater risk associated with monoclonal antibody constructs (e.g., adalimumab, infliximab) as compared with the pseudo-TNF receptor etanercept [ 128 , 129 ]. This latter phenomenon may in part be related to the ability of monoclonal antibodies to inhibit both soluble and transmembrane forms of TNF-α, whereas etanercept can only neutralize the soluble molecule, resulting in somewhat less potency and a concomitant lower risk of reactivation and dissemination [ 130 ].…”
Section: Asymptomatic Visceral Leishmaniasis: Emerging Issues In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Several common themes appear to have emerged, including an association with all forms of leishmaniasis, a generally typical disease presentation, a prolonged interval period between TNF-α inhibitor initiation and symptomatic disease onset (median of 18 months in one series), and a relatively greater risk associated with monoclonal antibody constructs (e.g., adalimumab, infliximab) as compared with the pseudo-TNF receptor etanercept [ 128 , 129 ]. This latter phenomenon may in part be related to the ability of monoclonal antibodies to inhibit both soluble and transmembrane forms of TNF-α, whereas etanercept can only neutralize the soluble molecule, resulting in somewhat less potency and a concomitant lower risk of reactivation and dissemination [ 130 ].…”
Section: Asymptomatic Visceral Leishmaniasis: Emerging Issues In Tmentioning
confidence: 99%
“…Treatment guidance for TNF-blockade associated VL is limited to the experience cited in case series; good outcomes with relatively low recurrence rates have been attained with standard anti-leishmanial therapies coupled with reduction in or temporary cessation of immunosuppression, and over 90% of patients can achieve clinical cure with this approach [ 125 , 129 ]. Zanger et al reported leishmanial recurrence in two of seven rechallenged patients (one cutaneous and the other mucosal leishmaniasis), with no relapses of VL in the other five.…”
Section: Asymptomatic Visceral Leishmaniasis: Emerging Issues In Tmentioning
confidence: 99%
“…In the era of biologics, physicians often witness the reactivation of latent infections, such as tuberculosis or leishmaniasis [1]. When it comes to leishmaniasis in relation to tumor necrosis factor alpha (TNF-α) inhibitors, one of the suggested pathogenetic mechanisms of infection is believed to be a TNF-α inhibitor-mediated downregulation of endothelial…”
Section: Discussionmentioning
confidence: 99%
“…Leishmaniasis is caused by an intracellular protozoon and is characterized by a broad spectrum of cutaneous, mucosal, and systemic presentations [1]. The clinical manifestations of leishmaniasis are determined by the subtype of the infectious agent and the immunocompetent profile of the patient [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation